Prevalence of Risk Factors of the Female Athlete Triad among Young Elite Athletes of Pakistan - Jaweria Syed; Anam Jamil; Nazma Namroz; Madiha Shakeel; Ayesha Malik; Sumaira Kanwal; Huma Riaz (International Journal of Sports Physical Therapy)
# Background